Pendampingan optimalisasi penggunaan media pembelajaran Bahasa Inggris sederhana untuk meningkatkan Creativity Quotient - Siti Ayu Surayya; Ari Prasetyaningrum; Lailawati Lailawati (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Madrasah Ibtidaiyah (MI) teachers still do not realize the importance of CQ (Creativity Quotient). It is seen from how the teachers tend to be consumptive and rely only on available media, like a material book. The purpose of this dedication is: 1) to bring over the meaning of CQ in MI level of education, 2) to improve the students’ studying quality, and 3) to maximize the function and university task to build the development of MI education. The method used in this dedication were speech, exhibition, and simulation of creative English language learning media made by the students in Hamzanwadi University and downloaded software media. This training was held in 2021, participated by 25 MI headmasters in the East Lombok district. The product of this training program is the MI headmaster spreading the use of learning media in MI. All MI teachers understand the importance of teaching media used as practical and creative learning tools, and the MI teachers become more creative in providing simple, cheap, and environmentally friendly.